The Revival of Trade Agreement Between Indonesia and Sudan: An Analytical Approach - Kurniawan, Hardiyono (Digital Repository of Theses - SSBM Geneva, 2025)
Taking the result of bilateral consultation in 2015 between the government of Indonesia and Sudan to increase trade and the fact that existing trade agreement is dormant into consideration, the need to revive bilateral trade agreement which will facilitate trade between Indonesia and Sudan is now relevant. The research then will assess the feasibility of a regional trade agreement (RTA) between Indonesia and Sudan using the Sussex Framework for assessing the RTA. Within the framework, the research then will measure the extent of feasibility of Indonesia and Sudan regional trade agreement. Afterward, the research will examine the competitiveness performance by measuring revealed comparative advantage and constant market share analysis indices. Based on these indices, the research will determine commodities that have the best performance and will be negotiated in tariff schedules within the proposed trade agreements. As the last step, the research will analyze the welfare impact of trade agreements by assessing the changes in trade policy, in this case the tariff reduction in the proposed trade agreements using a computable general equilibrium market simulation model. Based on the analysis, the research concluded that the RTA between Indonesia and Sudan have the prospect to be a successful RTA since the difference in initial tariff and degree of asymmetry and the product mix in trade pattern are in conformity with principle in the Sussex Framework in assessing RTA. Meanwhile, by simulating tariff reduction the research concluded that tariff reduction on the Sudanese side will bring indirect welfare impact for the both countries. Keywords: RTA, Sussex Framework, trade complementarity index, revealed comparative advantage, constant market share analysis, computable general equilibrium.